Smart cities’ development in Spain: a comparison of technical and social indicators with reference to european cities - Orejón-Sánchez, Rami David; Crespo García, David; Andrés-Díaz, José Ramón; Gago-Calderón, Alfonso (Sustainable Cities and Society, 2022)
The evolution of the Spanish cities towards their digital transformation, integration of the Internet of Things (IoT), and improvement of social cohesion have been promoted by the government. However, this evolution has not yet been evaluated, and this assessment is considerably relevant as more than 200 M€ has been spent from the European Regional Development Fund (ERDF) through five calls divided into two national plans (2014–2020). In this evaluation, the projects of 61 beneficiary local entities have been analysed. The lines of action executed have been identified and compared, using standardised indicators, with the actions conducted in the European metropolis that are smart city references. The actions planned in the last call (Smart Territories National Plan) closely resemble the philosophy of the latest generation paradigm of smart cities (holistic approach and specialisation in topics such as tourism or intelligent buildings) from the initial point where the areas of technology, software, and governance were focused. This work offers a precise picture of the priorities and lines of the progress of smart cities at each period of the last decade and helps technicians and investigators evaluate executed projects and design new lines of development.
Keywords: Ciudades - Efectos de las innovaciones tecnológicas; Smart mobility; Open data; Information and Communications Technology (ICT); Smart city; Internet of things (IoT)